Barndoms- og ungdomsminder fra Polen - Fish, Malka (Rambam. Tidsskrift for jødisk kultur og forskning, 2021)
This article describes my childhood years and youth in Poland in the 50s, 60s and early 70s. I grew up in a family of five including myself. My parents, my two older sisters and I lived poorly in an apartment in Wrocław, and anti-Semitism was a common phenomenon. Although I did not grow up in a religious home, I was always aware of my Jewish roots. I went to a Jewish kindergarten and a Jewish school, but neither of them was religious. At home we did not observe Jewish traditions, and our food was not always kosher. There were several Jewish families in our building and in our neighborhood in the 50s and we all helped each other and stuck together as if we were one big family. Throughout the 60s, however, many Jewish families emigrated leaving our family and a few others as the remaining Jews in a neighborhood that was now dominated by Christians. Nevertheless, Jewish cultural life in Poland flourished in the years after Stalin’s death. I particularly enjoyed the summer camps that took place every year. Here, I met many of my friends and my husband, whom I married when I was still very young. The birth of our first child coincided with the student demonstrations in Poland in the late 60s. Although he did not take part in the demonstrations, my husband was expelled from his university and was forced to do military service. I was left taking care of our two children – one more was born while my husband was away in the army – with no daycare center to help, and my parents were both ill. They immigrated to Israel in 1969 where my oldest sister was already living with her family. When they left, my mother-in-law moved in to help me with my children. Both my son and my daughter were chronically ill and had to be taken to a doctor often. Keeping a job at the same time was challenging, and at my work place they were very hostile to Jews, making my situation even more difficult. My husband returned from the army in 1970 and two years later we applied for permission to travel. We were turned down again and again. By the help of friends in Denmark I finally got permission to visit them in Copenhagen and without permission I also traveled to Israel to see my family and go to my father’s funeral. During my stay in Denmark, I decided that I wanted to come and live there with my family. We managed to trick the communist security service – they wanted us to report back to them regarding Danish warehouse prices – and in late December 1973 we left Poland permanently.